Sound, order and survival in prison: the rhythms and routines of HMP Midtown - Herrity, Kate (Bristol University Press, 2024)
The soundscape of prison life is that of constant clangs, bangs and jangles. What is the significance of this cacophonous din to those who live and work with it? This book is the story of a year spent with a UK prison community, bringing its social world vividly to life through aural ethnography --